AN EVALUATION OF MALAYSIA’S FOREIGN POLICY TOWARDS HAMAS IN THE BARISAN NASIONAL ERA - Imran, Muslim; Rogers, Roy Anthony; Balakrishnan, K S (Malaysian Journal of International Relations, 2025)
This paper examines Malaysia’s evolving relationship with Hamas during the Barisan Nasional era (1957–2018), focusing on the interplay of domestic politics, international pressures, and Islamic solidarity. Historically, Malaysia has been a steadfast supporter of the Palestinian cause, with varying degrees of engagement with Hamas. Under Prime Minister Najib Razak, Malaysia’s approach was characterised by humanitarian assistance and diplomatic support for Palestine, including visits to Gaza and interactions with Hamas leaders. Malaysia refrained from recognising the Western designation of Hamas as a “terrorist organisation”, maintaining diplomatic relations with the Palestinian Authority as well as Hamas, and supporting Palestinian unity. This study analyzes how Malaysia’s Islamic identity, domestic political considerations, and other foreign policy constraints influenced its stance towards Hamas. It also explores the implications of Malaysia’s position on its international relations, particularly with Western nations that classify Hamas as a terrorist entity. The findings suggest that Malaysia’s policy towards Hamas was a balancing act, aiming to uphold Islamic solidarity and domestic political interests while navigating complex international dynamics.